2017
DOI: 10.1159/000479793
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Bronchopulmonary Sequestration with Massive Pleural Effusion after Intrafetal Vascular Laser Ablation

Abstract: Objective: To assess the outcome of 12 fetuses with bronchopulmonary sequestration (BPS) and massive pleural effusion after intrafetal vascular laser ablation (VLA). Methods: All fetuses with BPS and massive pleural effusion that were treated with intrafetal VLA during a 5-year period (2012-2016) were reviewed for safety, intrauterine course, and postnatal outcome. Results: In the study period, 12 fetuses with BPS were treated with VLA. In 7 (58.3%) fetuses, complete cessation of blood flow was achieved after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…Other manners of prenatal treatment of sequestrations have been proposed by others, including the occlusion of the feeding vessel by ultrasound‐guided laser, radiofrequency ablation, and thrombogenic coil embolization, with mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Other manners of prenatal treatment of sequestrations have been proposed by others, including the occlusion of the feeding vessel by ultrasound‐guided laser, radiofrequency ablation, and thrombogenic coil embolization, with mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…However, in all these cases, the reported indication for the second procedure was the reappearance of blood flow in the feeding artery and it was not specified whether the hydrothorax had recurred. 20 Since fetal surgery is still associated to potential severe complications, 23,24 we believe that a repeat procedure should be indicated only in those cases in which recurrence of pleural effusion is noted in addiction to reperfusion of the mass. Cases in which blood flow in the feeding artery has recurred without signs of fetal hemodynamic compromise should be treated, in our opinion, as noncomplicated BPS in which the definitive treatment can be safely performed postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature identified 11 studies with original data of at least one case of BPS treated prenatally with USLC. 2,[12][13][14][15][16][17][18][19][20][21][22] Data on a total of 57 patients, including the five cases reported in the present series, were extrapolated and analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two complications were reported. First, fetal thoracic hematoma leading to fetal anemia complicated the procedure performed at 34 WG [15]. The fetus required postoperative blood transfusion.…”
Section: General Datamentioning
confidence: 99%